Photoacoustic Imaging of Animals with an Annular Transducer Array - 杨迪武 周智彬 曾吕明 周昕 陈星辉 (Chinese physics letters, 2014)
A photoacoustic system with an annular transducer array is presented for rapid, high-resolution photoacoustic tomography of animals. An eight-channel data acquisition system is applied to capture the photoacoustic signals by using multiplexing and the total time of data acquisition and transferring is within 3 s. A limited-view filtered back projection algorithm is used to reconstruct the photoacoustic images. Experiments are performed on a mouse head and a rabbit head and clear photoacoustic images are obtained. The experimental results demonstrate that this imaging system holds the potential for imaging the human brain.